2015
DOI: 10.1057/jphp.2015.32
|View full text |Cite
|
Sign up to set email alerts
|

Child toy safety: An interdisciplinary approach to unravel the microbiological hazard posed by soap bubbles

Abstract: In 2012 some children developed sepsis after playing together with a soap bubble toy. Microbiological testing revealed heavy contamination of the soap solution, which reasonably represented the vehicle of infection. We investigated the issue with a multidisciplinary approach: review of toy safety legislation; microbiological testing of additional samples; query of the RAPEX database for non-compliant soap bubbles; identification of major manufacturing districts. Microbiological contamination of industrial soap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…For this type of toy, between June 2009 and November 2014, the Safety Gate alert system received 63 product notifications across Europe that did not comply with the set microbiological parameters, 19 of which from Italy; 84% (16/19) of the Italian reports regarded an exceedance of the limits set for the aerobic microbial count at 30°C, whereas the presence of Ps. aeruginosa was observed in 32% (6/19) of reported cases (Amoruso et al, 2015). The authors report the presence of environmental bacteria and opportunistic pathogens, and the use of untreated water in the manufacture of soap bubbles.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For this type of toy, between June 2009 and November 2014, the Safety Gate alert system received 63 product notifications across Europe that did not comply with the set microbiological parameters, 19 of which from Italy; 84% (16/19) of the Italian reports regarded an exceedance of the limits set for the aerobic microbial count at 30°C, whereas the presence of Ps. aeruginosa was observed in 32% (6/19) of reported cases (Amoruso et al, 2015). The authors report the presence of environmental bacteria and opportunistic pathogens, and the use of untreated water in the manufacture of soap bubbles.…”
Section: Discussionmentioning
confidence: 98%
“…One Italian study showed that in summer 2012, young children developed symptoms such as lower limb pain, sore throat and fever after playing with a bottle of soap bubbles found to be contaminated with Pseudomonas aeruginosa (Amoruso et al, 2015). They were later diagnosed with bacterial sepsis based on blood tests and the blood culture presented a monoculture of Gram-negative Pseudomonadaceae.…”
Section: Introductionmentioning
confidence: 99%
“…The tremendous change in the number of reports for a limited time suggests an increased awareness of microbiological risks in toys. Our literature search on this topic revealed three cases of septicemia in children after playing with contaminated soap bubble toys in 2011 [16]. The case report in 2011 might have been the kickoff for the increasing trend of RAPEX alerts related to soap bubble toys, indicating an enhanced risk perception.…”
Section: Discussionmentioning
confidence: 99%
“…To date, data on the occurrence of microorganisms in toys are rare and patchy. The aforementioned case report describing an infectious outbreak among children who played with contaminated soap bubble toys identified P. aeruginosa as the causative pathogen [16]. Enterobacteriaceae were the second largest group identified in cosmetics and toys.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria Enterobacter genus is also found in soap bubble toys in Italy. The soap solution present in the toy is good for survival and possibly the growth of microorganisms [20].…”
Section: Discussionmentioning
confidence: 99%